First-line atezolizumab plus nab-paclitaxel for unresectable, locally advanced, or metastatic triple-negative breast cancer: IMpassion130 final overall survival analysis - Emens, Leisha Ann; Adams, S.; Barrios, C. H.; Diéras, V.; Iwata, H.; Loi, S.; Rugo, H. S.; Schneeweiss, Andreas; Winer, E. P.; Patel, S.; Henschel, V.; Swat, A.; et al. (Annals of oncology, 2021)
Background - Guidelines recommend atezolizumab plus nab-paclitaxel (A + nP) for first-line treatment of unresectable, locally advanced, or metastatic triple-negative breast cancer expressing programmed death-ligand 1 (PD-L1) on tumor-infiltrating immune cells (IC), based on IMpassion130. We report the final overall survival (OS) and safety of that study as per the prespecified analysis plan. - Patients and methods - Patients were randomized to nP 100 mg/m2 (days 1, 8, and 15 of a 28-day cycle) with atezolizumab 840 mg (A + nP) or placebo (P + nP; days 1 and 15), until progression or unacceptable toxicity. Coprimary endpoints were progression-free survival [intention-to-treat (ITT) and PD-L1 IC-positive populations] and OS (tested hierarchically in the ITT population and, if significant, in the PD-L1 IC-positive population). - Results - Each arm comprised 451 patients; 666 (73.8%) had died by the final OS analysis cut-off (median follow-up, 18.8 months; interquartile range, 8.9-34.7 months). Median OS in the ITT population was 21.0 months [95% confidence interval (CI), 19.0-23.4 months] with A + nP, and 18.7 months (95% CI, 16.9-20.8 months) with P + nP [stratified hazard ratio (HR), 0.87; 95% CI, 0.75-1.02; P = 0.077]. Exploratory analysis in the PD-L1 IC-positive population showed a median OS of 25.4 months (95% CI, 19.6-30.7 months) with A + nP (n = 185) and 17.9 months (95% CI, 13.6-20.3 months) with P + nP (n = 184; stratified HR, 0.67; 95% CI, 0.53-0.86). Safety outcomes were consistent with previous analyses and the known toxicity profiles of each agent. Immune-mediated adverse events of special interest were reported in 58.7% and 41.6% of patients treated with A + nP and P + nP, respectively. - Conclusion - Although the OS benefit in the ITT population was not statistically significant, precluding formal testing, clinically meaningful OS benefit was observed with A + nP in PD-L1 IC-positive patients, consistent with prior interim analyses. This combination remained safe and tolerable with longer follow-up.
Gesehen am 02.11.2021